On the equivalence between logic programming semantics and argumentation semantics - Caminada, Martin; Sá, Samy; Alcântara, João; Dvořák, Wolfgang (International journal of approximate reasoning, 2015)
In the current paper, we re-examine the connection between formal argumentation and logic programming from the perspective of semantics. We observe that one particular translation from logic programs to instantiated argumentation (the one described by Wu, Caminada and Gabbay) is able to serve as a basis for describing various equivalences between logic programming semantics and argumentation semantics. In particular, we are able to show equivalence between regular semantics for logic programming and preferred semantics for formal argumentation. We also show that there exist logic programming semantics (L-stable semantics) that cannot be captured by any abstract argumentation semantics. •We re-examine the equivalence between logic programming (LP) and argumentation.•One particular translation yields a whole range of semantic equivalences.•Notorious exception: L-stable (LP) and semi-stable (argumentation) do not coincide.•Several argumentation semantics operate by minimizing/maximizing argument labels.•Several LP semantics operate by minimizing/maximizing conclusion labels.